2017
DOI: 10.1128/iai.00327-17
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the β-Subunit of the RNA Polymerase Impair the Surface-Associated Motility and Virulence of Acinetobacter baumannii

Abstract: Acinetobacter baumannii is a major cause of antibiotic-resistant nosocomial infections worldwide. In this study, several rifampin-resistant spontaneous mutants obtained from the A. baumannii ATCC 17978 strain that differed in their point mutations in the rpoB gene, encoding the ␤-subunit of the RNA polymerase, were isolated. All the mutants harboring amino acid substitutions in position 522 or 540 of the RpoB protein were impaired in surface-associated motility and had attenuated virulence in the fertility mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…rpoB mutation in Clostridium difficile was associated with fitness cost in vitro and reduced virulence in vivo [21]. Mutations at position 522 or 540 in rpoB of A. baumannii were impaired in surface-associated motility and showed attenuated virulence [22]. The four different rpoB mutations in E. coli exhibited deleterious fitness costs under nutrient-rich conditions, but some rpoB alleles showed a remarkable fitness increase under phosphate limitation conditions [23].…”
Section: Discussionmentioning
confidence: 99%
“…rpoB mutation in Clostridium difficile was associated with fitness cost in vitro and reduced virulence in vivo [21]. Mutations at position 522 or 540 in rpoB of A. baumannii were impaired in surface-associated motility and showed attenuated virulence [22]. The four different rpoB mutations in E. coli exhibited deleterious fitness costs under nutrient-rich conditions, but some rpoB alleles showed a remarkable fitness increase under phosphate limitation conditions [23].…”
Section: Discussionmentioning
confidence: 99%
“…There were 27 codons changed in the rpoB gene of the L4650 strain. The number of mutations in the rpoB gene was higher than that in some previous reports (Hazen et al, 2009;Perez-Varela et al, 2017;Qazi et al, 2014). However, the bacterial strains in those reports were cultured in medium containing Rif with concentrations 40, 50 and 100 μg/ml, while L4650 strains were grown over many generations in medium containing Rif with gradually increasing concentrations (from 10 to 250 μg/ml).…”
Section: Discussionmentioning
confidence: 78%
“…The full-length of the rpoB gene was 4029 bp encoding a polypeptide with 1342 amino acids (Campbell et al, 2001). Mutations in the rpoB gene were found to be associated with Rif resistance of some bacterial strains such as Mycobacterium tuberculosis, Escherichia coli, Acinetobacter baumannii, Bacillus subtilis, V. parahaemolyticus (Hazen et al, 2009;Jin and Gross, 1988;Maughan et al, 2004;Perez-Varela et al, 2017;Zaw et al, 2018), and the mutation position would affect the level of the resistance to Rif (Taniguchi et al, 1996). Hazen et al (2009) reported that V. parahaemolyticus Rif-resistant strains with concentration at 100 µg/ml had the mutations in the rpoB gene (Hazen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, expression of a predicted operon for a taurine ABC transporter, consisting of four genes (A1S_1442-44), was downregulated in avnR deletion mutant. A1S_1443 that encodes for a predicted taurine ATP-binding transport system component has previously been associated with an involvement of surfaceassociated motility and virulence of A. baumannii [58] where the deletion of A1S_1443 abolished motility and was less virulent in a C. elegans model. Further, taurine is also believed to protect bacterial biofilms from osmotic stress [59].…”
Section: Deletion Of Avnr Affects Utilization Of Certain Nitrogen Soumentioning
confidence: 99%